Determinants of Foreign Direct Investment in Turkey: Empirical Evidence from ARDL Approach - Iweze, Charles; Akinsola, Gbenga Daniel; Olanrewaju, Victoria Olushola (Asian Development Policy Review, 2020)
Since the 1980s, there has been constant growth in Foreign Direct Investment (FDI), and in the previous 20 years, FDI has moved from advanced nations to developing economies. As they bring more growth prospects. Hence, this study looked critically in some selected factors that determine FDI in Turkey utilizing yearly data stretching 44 years (1974-2018). The objectives set for this study are; to ascertain influence of trade openness on FDI, to explore the interaction between FDI and economic growth in Turkey, and to verify if increase in Gross Capital Formation (GCF) will trigger FDI. ADF and PP, which are the conventional unit roots test and Zivot-Andrew unit root test, were utilized and the outcome reflects variables are stationary at mixed level. Thus, paving way for the estimation of the ARDL Bound test. Results from this test signify that variables are cointegrated in the long-run. Furthermore, the ARDL long run estimate depict increase in trade openness, and growth will triggers FDI in the long, though increase in gross capital formation will not trigger increase in FDI. The ARDL short-run estimate shows increase in GCF will trigger FDI. Recommendations were drafted based on these research findings.